2011
DOI: 10.1088/0253-6102/56/2/24
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Quantum Optical Springs and Their Nonclassical Properties

Abstract: The original idea of quantum optical spring arises from the requirement of quantization of the frequency of oscillations in the Hamiltonian of harmonic oscillator. This purpose is achieved by considering a spring whose constant (and so its frequency) depends on the quantum states of another system. Recently, it is realized that by the assumption of frequency modulation of ω to ω 1 + µa † a the mentioned idea can be established. In the present paper, we generalize the approach of quantum optical spring with par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…where the effect of intensity-dependent coupling has been studied, it is observed that this effect [of course, by considering the chosen nonlinearity function f i n i n i p ] decreases the amount of negativity of entropy squeezing. Finally, we would like to emphasize the generality of our obtained formalism in the sense that it may be used for any physical system, either any nonlinear oscillator algebra with arbitrary nonlinearity function, or any solvable quantum system with known discrete energy spectrum e n [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…where the effect of intensity-dependent coupling has been studied, it is observed that this effect [of course, by considering the chosen nonlinearity function f i n i n i p ] decreases the amount of negativity of entropy squeezing. Finally, we would like to emphasize the generality of our obtained formalism in the sense that it may be used for any physical system, either any nonlinear oscillator algebra with arbitrary nonlinearity function, or any solvable quantum system with known discrete energy spectrum e n [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] In this respect, as we shall see later, the quantum states of interest, which will be introduced in the next section, illustrate how they can significantly be found as good candidates for nonclassical states of light in the presence of intensity‐dependent nonlinearity function. This is because of convincing evidence for nonlinear CSs such as displaced excited CSs, [ 43 ] nonlinear quantum optical spring, [ 44 ] nonlinear semi‐CSs, [ 45 ] f ‐deformed charge CSs, [ 46 ] nonlinear motional trio CSs, [ 47 ] and nonlinear elliptical states, [ 48 ] all of which obviously demonstrate the nonclassicality features of light.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nonlinear coherent states, which are known as a natural generalization of canonical coherent states (corresponding to simple harmonic oscillator) to f -deformed ones (associated with nonlinear oscillators) [15,16], can be considered as suitable candidates from which nonclassical light comes out [24,25,26,27,28]. It is worthwhile to mention that, there exist many generalized coherent states categorizing in this special class of quantum states, which exhibit the nonclassicality features of light, i.e., 'nonclassical' light [29,30,31].…”
Section: Introductionmentioning
confidence: 99%